Two novel EIF2AK3 mutations in a Chinese boy with Wolcott-Rallison syndrome - Feng, Dai-Rong (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2011)
OBJECTIVE: Wolcott-Rallison syndrome (WRS) is a rare autosomal recessive disorder characterized by the association of permanent neonatal or early-infancy insulin-dependent diabetes, multiple epiphyseal dysplasia and growth retardation, and other variable multisystem clinical manifestations. Here we describe a Chinese boy affected by WRS. Genetic testing of his EIF2AK3 gene was performed in order to elucidate molecular variations and subsequently to provide credible genetic counseling for prenatal diagnosis in his family